Metafora Ekologis: Struktur Tasybih dan Implikasi Semantiknya dalam Hadis-Hadis Kelestarian Lingkungan - Mareta Asprianti; AangSaeful Milah; Siti Intan Ceputri; TriWidya Oktaviani; Ahmad Maulana (LPPM IAI Pangeran Dharma Kusuma Segeran Indramayu, 2026)
The anthropogenic global environmental crisis demands an ethical-spiritual reorientation that transcends secular technocratic regulations, one of which is through the excavation of prophetic religious texts. This study aims to unravel the characteristics of the stylistic structure of tasybih (similarity) in environmental sustainability hadiths and reveal their semantic implications for the formation of human ecological awareness. A qualitative approach with interdisciplinary textual analysis is applied using the classical Bayan Science framework (Al-Jurjani and Al-Qazwini's tasybih theory) integrated with the concept of contemporary ecological metaphor. Data sources were obtained through purposive sampling of canonical hadith books (al-Kutub al-Sittah), resulting in 5 representative environmental hadiths to be manually analyzed using an analysis tabulation sheet. The results of this study indicate that prophetic environmental rhetoric is dominated by the typologies of Tasybih Mu'akkad and Tasybih Baligh, which consistently eliminate the customary component of al-tasybih (connections) and the use of isti'arah makniyyah (personification). The semantic implications of this ecological metaphorical structure successfully narrow the ontological distance between human actions and nature; flora is reconceptualized as an instrument of continuous eschatological reward (interspecies alms), water is placed under strict consumption quotas, and critical land is personified as a living organism with an existential right to life (ihya al-mawat). Theoretically, these findings reposition the flexible function of classical Balaghah as a tool for analyzing modern secular crises, while also providing a practical contribution to the formulation of a more persuasive theological-aesthetic-based ecological campaign narrative for the global Muslim community.